2022
DOI: 10.1051/shsconf/202214903034
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Community Empowerment and Organizational Behaviour on Satisfaction and Performance of the Salt Industry in Sumenep

Abstract: This study examines the effect of community empowerment and organizational behavior on the satisfaction and performance of salt farmers in Sumenep Regency. This research is a quantitative research that examines the influence between variables. Data collection techniques using questionnaires distributed to respondents. The population of this research is 57 salt farmers with the population using the census technique, namely by using the entire population. The results of the analysis show that there is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…It provides empirical evidence that a key precondition for employee contextual performance is work effectiveness. This finding is consistent and confirms previous studies which claim that work effectiveness has a significant effect on contextual performance (e.g., Arifin & Akhmad, 2022;Arifin & Hidayat, 2023;Rani et al, 2021) and at the same time is an antithesis to Afram et al's study. (2022) and Jiang and Liu (2015) that work effectiveness does not influence performance and performance actually influences effectiveness.…”
Section: Hypothesis Testingsupporting
confidence: 93%
See 3 more Smart Citations
“…It provides empirical evidence that a key precondition for employee contextual performance is work effectiveness. This finding is consistent and confirms previous studies which claim that work effectiveness has a significant effect on contextual performance (e.g., Arifin & Akhmad, 2022;Arifin & Hidayat, 2023;Rani et al, 2021) and at the same time is an antithesis to Afram et al's study. (2022) and Jiang and Liu (2015) that work effectiveness does not influence performance and performance actually influences effectiveness.…”
Section: Hypothesis Testingsupporting
confidence: 93%
“…So far, no research has been found proving that work effectiveness mediates the influence of workplace spirituality on employees' contextual performance. However, these findings confirm several previous relevant studies which prove that workplace spirituality impacts effectiveness (Daniel, 2010;Kusnadi & Prijono, 2023), work effectiveness affects performance (Arifin & Akhmad, 2022;Arifin & Hidayat, 2023;Rani et al, 2021;Tuffaha, 2020;Assbeihat, 2016;Tsai & Tsai, 2017), and workplace spirituality influences performance (Nwanzu & Babalola, 2021;Jena, 2021;Ekowati, 2022). As shown in testing H3, workplace spirituality has a direct positive effect on employees' work effectiveness.…”
Section: Hypothesis Testingsupporting
confidence: 89%
See 2 more Smart Citations